Preoperative Iodine Staining May Complicate the Demarcation of Esophageal Carcinoma (Gut and Liver, 2013)
A 53-year-old man was suspected of having an esophageal neoplasm. An endoscopic examination including Lugol chromoendoscopy suggested an esophageal squamous cell neoplasm limited to the lamina propria. A targeted biopsy showed atypical squamous cells, and an endoscopic submucosal dissection was performed 22 days after the previous endoscopy. Although a single 40 mm unstained area was observed by preoperative Lugol chromoendoscopy, intraoperative endoscopy revealed a 25 mm iodine-unstained area, with small unstained areas scattered on the oral side. We included the small unstained areas in the extent of the resection through assessment by preoperative endoscopy. Histopathologically, the tumor extent appeared to coincide with the preoperative assessment. Tumor cells were found in the basal-parabasal layers of the mucosa, in which small unstained areas were scattered, although the superficial layers exhibited well-differentiated cells containing glycogen in the cytoplasm. Although Lugol chromoendoscopy, which can induce chemical esophagitis, is widely used, re-epithelialization after mucosal damage by preoperative iodine staining may complicate the intraoperative demarcation of tumors.